Singapore's economic development retrospection and reflections - Lim, Linda; Lee, Soo Ann 1939- (World Scientific series on Singapore's 50 years of nation-building, 2016)
"Singapore is known internationally for its successful economic development. Key to its economic successes is a variety of policies put into place over the past 50 years since its independence. Singapore's Economic Development: Retrospection and Reflections provides a retrospective analysis of independent Singapore's economic development, from the perspective of different policy domains each considered by different expert scholars in that particular field. The book is written by academic economists in a style that is accessible to non-experts. Each chapter includes reviews of past scholarship, current data on each policy area, and reflections on required or desirable future policy changes and outcomes"--Provided by publisher.